Lack of micronucleus induction by ‘Sobatum’ in bone marrow erythrocytes of Swiss mice - Mohanan, P.V.; Rathinam, K.; Devi, K.S. (Mutation Research/Environmental Mutagenesis and Related Subjects, 1996)
The plant Solanum trilobatum is mainly used for asthma, chronic febrile affections and difficult parturition. The active principle (Sobatum) obtained from the petroleum ether extract of the plant was proved as an anticancer agent by in vitro and in vivo experiments. Here, an effort was made to evaluate the induction of micronucleus by the Sobatum in the bone marrow of swiss mice. The micronucleus assay was conducted after 24 and 72 h of second administration of the Sobatum. The first set of experiments (24 h after second administration) consisted of 4 groups with 3 male Swiss albino mice each. The first group (as control) received only dimethyl sulfoxide, the second, third and fourth groups received different doses of the Sobatum (100, 200, 400 mg/kg body weight), and the fifth group (as positive control) received cyclophosphamide (100 mg/kg body weight) by i.p. injection. In the second set of experiment (72 h after the second administration) consisting of 5 groups, the first, as control, received dimethyl sulfoxide, the second, third and fourth groups received different concentrations of the Sobatum (100, 200, 400 mg/kg body weight), and the fifth group as positive control received cyclophosphamide (100 mg/kg body weight). All the animals of the first and second sets of experiment were killed 24 and 72 h after the second medication (2 consecutive days), and bone marrow smears were prepared, stained with May-Grunwald and Giemsa stain, and evaluated for the evidence of micronucleus. The study concluded that the Sobatum fails to influence the induction of micronuclei in bone marrow erythrocytes of mice 24 and 72 h after the second administration, thereby proving that Sobatum to has no cytogenetic toxic potential.